IN VITRO STUDIES AND AGROBACTERIUM RHIZOGENES MEDIATED TRANSFORMATION OF CISSAMPELOS PAREIRA – A HIGHLY RECALCITRANT SPECIES - VIKASH SHAD,; DEEPA M.A,; DEEPA M.A, (International Journal of Pharma and Bio Sciences, 2016)
An attempt was made to induce callus mediated regeneration of Cissampelos pariera plants using leaf explants along with induction of hairy root for increasing the secondary metabolites. A4, MSU 440, K599, NCIM 5140 and 9402 strains of A. rhizogenes was used for hairy root induction. Transformation using liquid co-cultivation, direct introduction of cultures into wound site and also sonication assisted cocultivation methods. The leaf explants cultured on MS medium supplemented with NAA (2mg/l) showed proliferation of callus. But the callus failed to show organogenesis on MS media enriched with any growth hormones. The plant species were highly recalcitrant. Among the methods and strain used for hairy root culture, the leaves co-cultured with A. rhizogenes strain MSU440 using sonication-assisted method alone showed callus formation on MS Medium devoid of growth hormones. The callus subjected to HPLC analysis showed the increase in Berberine content.